Peningkatan Administrasi Penyiaran Radio Republik Indonesia Di RRI Padang - desmeynellis; David Saputra (LPPM STISIP IMAM BONJOL, 2024)
The aim of this research is to: 1) describe how the broadcasting administration of Radio Republik Indonesia has improved in the midst of the digital era. 2) describe the obstacles and efforts in improving the broadcasting administration of Radio Republik Indonesia in the midst of the digital era. This research uses a qualitative type of research. Bogdan and Taylor (in Moleong, 2016) define qualitative methods as research procedures that produce descriptive data in the form of spoken written words from people and observable behavior. The data sources are primary data and secondary data collected through observation, interviews and documentation. In this research, the researcher used key research informants, namely the Head of LPP RRI Padang, 1 person, Head of Administration, 1 person, 5 employees. The data collection techniques used in this research are observation, interviews and documentation. The research results of Radio RRI Padang also rely on human resources such as broadcasters. Where broadcasters are an important factor so that listeners can continue to listen to every broadcast that is broadcast. Delivery techniques and how the announcer can get close to the listener are one of the mainstay keys carried out on RRI Padang radio. Radio RRI Padang has the principle that if an announcer's delivery is able to captivate listeners, then of course listeners will continue to listen and of course this is what will make Radio RRI Padang survive in this digital era